A holistic approach to sustainability in higher education institutes: social, economic, educational, and mobility perspectives - Barnett-Itzhaki, Zohar; Tifferet, Sigal; Etstein, Yaeli; Gefen, Inna; Ravid, Oded; Barokas, Guy; Vilnai-Yavetz, Iris; Carasso Romano, Gal Hagit; Levi, Adi (Frontiers in Education, 2025)
Higher education institutions (HEIs) are pivotal in driving the transition to sustainability. HEIs educate future generations and adopt sustainable practices, setting an example for private and public sector organizations. This paper reviews studies and initiatives covering the fields of education, physical/mental health, economy, social sustainability, and transportation. This review aims to: (1) Identify key obstacles hindering the implementation of sustainable HEI practices. (2) Explore measures/indicators to evaluate the effectiveness of HEI sustainability initiatives. (3) Provide key recommendations to promote sustainability in HEIs. Our conclusions emphasize the critical role of HEIs in advancing social sustainability. Recommendations include developing sustainability plans, integrating sustainability into academic programs, enhancing health and well-being, ensuring economic viability through cost–benefit analyses, and promoting sustainable transportation. Stakeholder engagement, strategic assessment, and transparent reporting are essential for accountability and improvement. By implementing these strategies, HEIs can establish resilient and sustainable communities, serving as exemplary models for broader societal change.